Crorepati Zehan Kay Raaz - Eker, T. Harv (Faisalabad Peace Books, 2017)
In his groundbreaking Secrets of the Millionaire Mind, T. Harv Eker states: "Give me five minutes, and I can predict your financial future for the rest of your life!" Eker does this by identifying your "money and success blueprint." This blueprint determines your financial life. If your money blueprint is not set for a high level of success, you will never have a lot of money -- and if somehow you do, you will most likely lose it! The good news is that now you can actually reset your money blueprint to create natural and automatic success.In Secrets of the Millionaire Mind, you will learn how your childhood influences have shaped your financial destiny. You will also learn how to identify your own money blueprint and "revise" it to not only create success but, more importantly, to keep and continually grow it. Finally, you will be introduced to the "Wealth Files:" 17 specific ways rich people think and act. These include specific action steps for you to practice in order to increase your income and accumulate wealth. It's simple, if you think like rich people think and do what rich people do, chances are you'll get rich too!
Keywords: Millionaires--Psychology -- Money--Psychological aspects -- Success in business--Psychological aspects